Physician-reported Clinical Unmet Needs, Burden and Treatment Patterns of Paediatric Psoriasis Patients: A US and EU Real-world Evidence Study - Marieke M.B. Seyger; Matthias Augustin; Michael Sticherling; Teresa Bachhuber; Juanzhi Fang; James Hetherington; James Lucas; Sophie Meakin; Craig Richardson; Amy S. Paller (Medical Journals Sweden, 2022)
This study is a retrospective analysis using data collected from the Adelphi Paediatric Psoriasis Disease-Specific Programme cross-sectional survey. Despite being treated for their psoriasis, a substantial proportion of paediatric patients presented with moderate (18.3%) or severe (1.3%) disease at sampling; 42.9% and 92.0% had a body surface area (BSA) of >10%, and 38.8% and 100.0% had a Psoriasis Area Severity Index (PASI) score >10, respectively. Overall, 69.9% of patients had only ever been treated with a topical therapy for their psoriasis. For patients with moderate or severe disease at sampling, 16.3% and 14.4% were currently receiving conventional systemics or biologic therapy, respectively. There is a clinical unmet need in this paediatric population; a considerable percentage of patients still experienced moderate or severe disease and persistent psoriasis symptoms, with numerous body areas affected. A significant proportion of patients were undertreated, which may explain the high burden of disease observed.